Breaking the spell of war - Ivie, Robert L. (Javnost (Ljubljana), 2009)
This essay examines and extends peace journalism's critique of mainstream news media in order to articulate a model of an enriched news narrative resistant to war propaganda and consistent with democratic praxis. It discusses the potential of political myth to delimit demonising projections that otherwise debilitate democratic deliberation and suggests that news media would advance democratic culture by enhancing the public archive on which deliberative practices depend. Critical attention is focused on two factors that reduce the democratic potential of news narratives: (1) the persistent omission of key information and (2) a chronic imbalance in interpretive frames. Whether or not professional conventions and market considerations render corporate media incapable of correcting truncated and unbalanced news narratives, the capacity of the public archive to support democratic deliberation corresponds to the knowledge and perspective it accrues to curtail alienating projections. We must ask, then, if democracyćs deliberative prospect can be realised short of correcting the shortcomings of news media.
Keywords: journalism; novinarstvo; informiranje; svoboda informiranja; objektivnost; democracy; demokracija; vojna; war; vojna propaganda; mir